(untitled) (Research, Society and Development, 2022)
Objectives: Identify whether health professionals report adverse events related to medication errors and analyze the factors that lead them not to report adverse events, in addition to discussing the main medication errors commited by health professionals. Methodology: This is an integrative, descriptive and qualitative literature review, which used the PICO strategy to elaborate the following question: Do health professionals report adverse events related to medication errors in pediatrics and what factors lead them not to do so? Data collection was carried out between December 2021 and March 2022. The following databases were used: LILACS, MEDLINE, Cochrane Library and Scopus®. The descriptors used were: (“medication errors”), (“child”), (“pediatrics”) and (“notice”), using the boolean operators AND and OR. Results: 10 articles were selected that discuss the notifications of adverse events related to medicines in pediatrics and it was observed that most of the production was concentrated abroad, especially in Europe. Half of the studies performed and/or proposed interventions to improve practices for reporting adverse drug events. However, many surveys used surveillance and/or reporting pharmacovigilance systems from their country to carry out the same studies (40%). Conclusion: Strategies on medication errors aim to promote and disseminate patient safety as well as minimize the occurrence of errors. It should be based on increasing the level of staff confidence, greater clarity and training on reporting systems.